Low frequency of cigarette smoking and the risk of head and neck cancer in the INHANCE consortium pooled analysis - Berthiller, Julien; Straif, Kurt; Agudo, Antonio; Ahrens, Wolfgang; Bezerra Dos Santos, Alexandre; Boccia, Stefania; Cadoni, Gabriella; Canova, Cristina; Castellsague, Xavier; Chen, Chu; Conway, David; Curado, Maria Paula; et al. (International journal of epidemiology, 2016)
BACKGROUND: Cigarette smoking is a major risk factor for head and neck cancer (HNC). To our knowledge, low cigarette smoking (<10 cigarettes per day) has not been extensively investigated in fine categories or among never alcohol drinkers. METHODS: We conducted a pooled analysis of individual participant data from 23 independent case-control studies including 19 660 HNC cases and 25 566 controls. After exclusion of subjects using other tobacco products including cigars, pipes, snuffed or chewed tobacco and straw cigarettes (tobacco product used in Brazil), as well as subjects smoking more than 10 cigarettes per day, 4093 HNC cases and 13 416 controls were included in the analysis. The lifetime average frequency of cigarette consumption was categorized as follows: never cigarette users, >0-3, >3-5, >5-10 cigarettes per day. RESULTS: Smoking >0-3 cigarettes per day was associated with a 50% increased risk of HNC in the study population [odds ratio (OR) = 1.52, 95% confidence interval (CI): (1.21, 1.90). Smoking >3-5 cigarettes per day was associated in each subgroup from OR = 2.01 (95% CI: 1.22, 3.31) among never alcohol drinkers to OR = 2.74 (95% CI: 2.01, 3.74) among women and in each cancer site, particularly laryngeal cancer (OR = 3.48, 95% CI: 2.40, 5.05). However, the observed increased risk of HNC for low smoking frequency was not found among smokers with smoking duration shorter than 20 years. CONCLUSION: Our results suggest a public health message that low frequency of cigarette consumption contributes to the development of HNC. However, smoking duration seems to play at least an equal or a stronger role in the development of HNC.
Keywords: senioři; nádory hlavy a krku; risk factors; Male; Public Health; Middle Aged; mužské pohlaví; Head and Neck Neoplasms; studie případů a kontrol; Adult; kouření cigaret; logistické modely; pooled analysis; ženské pohlaví; Humans; odds ratio; lidé středního věku; Head and neck cancer; Cigarette Smoking; rizikové faktory; Alcohol Drinking; pití alkoholu; Logistic Models; low frequency cigarette smoking; dospělí; Female; veřejné zdravotnictví; Aged; Risk Factors; lidé; Case-Control Studies; Odds Ratio